Food and nutrition customs and culture - Fieldhouse, Paul (Chapman & Hall, 1995)
Whilst all people have to eat to live, what they eat is largely determined by their cultural influences. Through developing an appreciation of the central role that food plays in people's lives, professionals concerned with nutrition education may increase both the relevance and effectiveness of what they do. This long awaited second edition focuses on the social and biocultural uses of food in ancient and contemporary societies throughout the world. Food and Nutrition will be an invaluable resource for all professionals and students in health related disciplines, such as dietetics, nutrition, nursing and health education.